(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
The article deals with topical issues of increasing the economic potential of textile enterprises of Uzbekistan in the conditions of increasing global competition. Foreign experience of textile industry development and domestic methods of modernisation of enterprises are compared.